PERBEDAAN TINGKAT KECEMASAN PASIEN ANAK USIA PRASEKOLAH SEBELUM DAN SESUDAH PROGRAM MEWARNAI - Ameliorani Pravitasari; Bambang Edi Warsito (Jurusan Keperawatan, Universitas Diponegoro, 2012)
The childrens in 3 up to 6 years old (preschool), hospitalize is stressor which is influance child growth. Fearness about unusual situation, nurse in white, injure prossedure, separation with parent and loose their freedom to play will make them get anxiety. The over anxiety like reject to eat, defficult to sleep and cry more and more will delay curative treatment and make patient get bad experience after hosptalized. Purpose of this research is to know the difference anxiety between pre and post colouring program. This research used one group pre-post test pre experiment quantitative method and researcher got 20 patients in 3 up to 6 years old on RSUD Ungaran as samples. The datas took used check list with observation and interview method. Analyzed result used T-Test Paired was 15,636 from table T = 2,145. The research conclution was the different anxiety preschool patient before and after did colouring program in RSUD Ungaran. This reasearch need take more reasearch with more samples and longer time so that get more valid result